Prevalence of cryptosporidiosis in dairy cattle, cattle-keeping families, their non-cattle keeping neighbours and HIV-positive individuals in Dagoretti Division, Nairobi, Kenya - Kang'ethe, Erastus K.; McDermott, B.; Grace, Delia; Mbae, C.; Mulinge, E.; Monda, J.; Nyongesa, C.; Ambia, J.; Njehu, A. (Springer, 2012)
This paper reports a study estimating the prevalence of cryptosporidiosis, an emerging zoonosis, in people and cattle in Dagoretti, Nairobi. A repeated cross-sectional survey was carried out among randomly selected cattle keepers in Dagoretti, their dairy cattle and their non-cattle-keeping neighbours in the dry and wet seasons of 2006. A survey was also carried out among a group of people living with human immunodeficiency virus (HIV). Faecal samples were examined for Cryptosporidium oocysts using the modified Ziehl–Neelsen method; 16 % of the samples were also examined using immunofluorescence antibody (IFA) technique. Quality control consisted of blind reviews of slides, examining split samples and confirming slide results with IFA. We found that members of dairy households had a dry season cryptosporidiosis prevalence of 4 % and wet season prevalence of 0.3 %, and non-dairy households, a prevalence of 5 and 0 %, respectively. The cattle dry season prevalence was 15 %, and the wet season prevalence, 11 %. The prevalence in people living with HIV was 5 %. The laboratory quality control system showed some inconsistency within and between different tests, indicating challenges in obtaining consistent results under difficult field and working conditions. In conclusion, this is the first reported study to simultaneously survey livestock, livestock keepers and their neighbours for cryptosporidiosis. We failed to find evidence that zoonotic cryptosporidiosis is important overall in this community. This study also draws attention to the importance of quality control and its reporting in surveys in developing countries.